The role of Ulama and Malay customary institutions in shaping voters' political preferences in the 2024 regional elections in Riau - Wardana, Data; Wijaya, Mendra; Juliana, Septa; Hendrik, Doni (Frontiers in Political Science, 2025)
This study aims to analyze the influence of religious scholars and Malay traditional institutions on the political preferences of the community. In this context, religious scholars are defined as religious figures who have a significant influence in shaping the views and attitudes of the community toward political issues, while Malay customary institutions refer to social structures that regulate norms and values in Malay society. This study uses a quantitative approach with multiple linear regression analysis, which is a statistical method that allows researchers to understand the relationship between several independent variables and one dependent variable. This study uses a quantitative approach with multiple linear regression analysis, which is a statistical method that allows researchers to understand the relationship between several independent variables and one dependent variable. The results indicate that the role of ulama has a significant influence on political preferences (p = 0.003), while the role of customary institutions does not have a considerable impact (p = 0.416). This study highlights a shift in socio-political authority from customary institutions to ulama in shaping political preferences in Riau Province. These findings confirm a shift in social-political authority from traditional institutions to religious figures in society. The greater the influence of religious scholars in society, the greater the likelihood that the community will choose political candidates or parties that align with the teachings and views of religious scholars. It is recommended that the cultural role of traditional institutions be strengthened and that other factors influencing the formation of political preferences be explored.